Prevalence of Coronavirus Antibody Among First Responders in Lubbock, Texas. (November 2020) - Iwuji, Kenneth; Islam, Ebtesam; Berdine, Gilbert; Nugent, Kenneth; Test, Victor; Tijerina, Amanda
Background: The ongoing coronavirus disease (COVID-19) pandemic has a major impact on first responders. Scarce personal protective equipment (PPE) has forced them to conserve and reuse some of their PPE. The efficacy of these practices in preventing transmission of COVID-19 from patients to first responders is unclear. There are limited data on the prevalence of antibodies specific for COVID-19 exposure in these front-line workers. Aim: Our objective was to determine the prevalence of positive immunoglobulin G antibody specific to COVID-19 among first responders in Lubbock, Texas. Methods: Blood samples were collected on 683 asymptomatic first responders who work in Lubbock, Texas and the surrounding area, after informed consents were signed. IgG antibody to SARS-CoV-2 was measured using Abbott's SARS-CoV-2 IgG Reagent Kit in combination with the SARS-CoV-2 IgG Calibrator Kit on the Abbott's ARCHITECT i 1000SR analyzer. Results: The prevalence of IgG specific antibodies to COVID-19 was 0.73%, five of the 683 participants tested positive. Four of those who tested positive had no known prior SARS-CoV-2 infection or exposure without adequate PPE. Conclusions: The prevalence of IgG specific antibodies to COVID-19 was much lower than expected in our study population despite high sensitivity and specificity of the test reagent. The most likely explanations for this finding include limited exposure, inadequate time for a IgG response, possible clearance of COVID-19 infection locally by the respiratory tract IgA defense system without eliciting a systemic IgG response, and short persistence of IgG antibodies in mild or asymptomatic cases.